HyProCure for Pediatric Flexible Flatfoot: What Affects the Outcome - Chen, Cheng; Jiang, JianTao; Fu, ShaoLing; Wang, Cheng; Su, Yan; Mei, GuoHua; Xue, JianFeng; Zou, Jian; Li, XueQian; Shi, ZhongMin (Frontiers in Pediatrics, 2022)
Background The high success rate, minimal invasion, and safety of subtalar arthroereisis (SA) have made it a primary mode of surgical management for pediatric flexible flatfoot. The HyProCure procedure is a new surgery for SA, However, very few available studies reported the therapeutic effects of the HyProCure procedure, especially in pediatric flexible flatfoot. The main aim of the present study was to investigate the clinical and radiological outcomes of the HyProCure procedure for pediatric flexible flatfoot and analyze the risk factors for therapeutic outcomes and sinus tarsi pain. Methods In this retrospective cohort study, 69 pediatric flexible flatfoot patients (107 feet) who underwent the HyProCure procedure were included between July 2015 and September 2020. All patients underwent the HyProCure procedure with or without gastrocnemius recession. The Maryland foot score (MFS), visual analog scale (VAS), radiographic data, and complications were assessed at a minimum 1-year follow-up and statistically analyzed. Results The mean follow-up was 35.9 months (range, 13–73 months). At the last follow-up, VAS (0.64 ± 1.16) was significantly lower than the preoperative VAS (4.06 ± 1.43) (p < 0.001); MFS (90.39 ± 12.10) was significantly higher than the preoperative MFS (71.36 ± 10.25) (p < 0.001). The AP talar-second metatarsal angle (T2MT angle) significantly decreased from 17.0 ± 5.4° preoperatively to 11.4 ± 5.2° at the last follow-up (p < 0.001). The lateral talar-first metatarsal angle (Meary's angle) significantly decreased from 13.8 ± 6.4° preoperatively to 6.3 ± 5.0° at the last follow-up (p < 0.001). The calcaneal declination angle (Pitch angle) significantly increased from 13.5 ± 4.9° preoperatively to 14.8 ± 4.4° at the last follow-up (p < 0.001). Logistic regression analysis indicated that patients with a longer distance from the tail end of the implant exceeding the longitudinal talar bisection line had 275.8% greater odds of MFS < 90. Yet, no risk factors were found in connection with sinus tarsi pain. Conclusions The HyProCure procedure for pediatric flexible flatfoot achieved satisfactory curative effects with a low complication rate; implant depth was associated with unsatisfactory postoperative outcome.